Management-level officers’ experiences with the Ferguson Effect - Nix, Justin (2018)
Purpose The purpose of this paper is to examine the factors associated with management-level officers’ sensitivity to various manifestations of the “Ferguson effect.” Design/methodology/approach A survey was administered to police officers attending an advanced training institute in the Southeastern USA in the fall of 2015. Specifically, a series of items first inquired about negative attitudes attributable to deadly force incidents throughout the country, followed by items tapping into theoretically relevant concepts including self-legitimacy, audience legitimacy, and peer attachment. Findings Findings suggest that like line-level officers, police managers may also harbor various attitudes attributable to a Ferguson effect – including less willingness to be proactive, reduced motivation, less job enjoyment, and a belief that crime will ultimately rise as officers “de-police.” However, officers who believe their communities afford legitimacy to the police were less likely to report these sentiments. Study limitations and avenues for future research are also discussed. Originality/value This is the first study to consider how police managers have been impacted by highly publicized deadly force incidents in recent years. It underscores the importance of maintaining legitimacy in the public eye, particularly in the post-Ferguson era of American policing